Potential Role of Traditional Birth Attendants in Neonatal Healthcare in Rural Southern Nepal - Falle, Tina Y; Mullany, Luke C; Thatte, Nandita; Khatry, Subarna K; LeClerq, Steven C; Darmstadt, Gary L; Katz, Joanne; Tielsch, James M (Journal of Health, Population and Nutrition, 2009)
The potential for traditional birth attendants (TBAs) to improve neonatal health outcomes has largely been overlooked during the current debate regarding the role of TBAs in improving maternal health. Randomly-selected TBAs (n=93) were interviewed to gain a more thorough understanding of their knowledge, attitudes, and practices regarding maternal and newborn care. Practices, such as using a clean cord-cutting instrument (89%) and hand-washing before delivery (74%), were common. Other beneficial practices, such as thermal care, were low. Trained TBAs were more likely to wash hands with soap before delivery, use a clean delivery-kit, and advise feeding colostrum. Although mustard oil massage was a universal practice, 52% of the TBAs indicated their willingness to consider alternative oils. Low-cost, evidence-based interventions for improving neonatal outcomes might be implemented by TBAs in this setting where most births take place in the home and neonatal mortality risk is high. Continuing efforts to define the role of TBAs may benefit from an emphasis on their potential as active promoters of essential newborn care. Key words: Community-based interventions; Knowledge, attitudes, practices; Neonatal mortality; Traditional birth attendants; Nepal doi: 10.3329/jhpn.v27i1.3317 J Health Popul Nutr 2009 Feb;27(1):53-61